2009 47th Annual Allerton Conference on Communication, Control, and Computing (Allerton) 2009
DOI: 10.1109/allerton.2009.5394925
|View full text |Cite
|
Sign up to set email alerts
|

Limited lookahead supervisory control of probabilistic discrete-event systems

Abstract: Limited lookahead control policies adapt the concept of supervisor synthesis in discrete-event systems (DES) to work for very large and/or dynamic systems. This is accomplished by considering an N-step projection of possible behaviours of the system, instead of dealing directly with the entire system. This paper builds on previous work to produce a limited lookahead algorithm that incorporates probabilistic event occurrences and a desirability function for strings of events. An example is used to compare the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…For example, they can be a function of time, of past performance and/or of current system composition. For example, in [15], the authors propose a framework where the supervisor may choose to switch between a number of control policies during runtime.…”
Section: A Control Specificationsmentioning
confidence: 99%
“…For example, they can be a function of time, of past performance and/or of current system composition. For example, in [15], the authors propose a framework where the supervisor may choose to switch between a number of control policies during runtime.…”
Section: A Control Specificationsmentioning
confidence: 99%
“…They concluded that RUBLL's performance was consistent with the optimal solution but was more readily applied to scenarios where exhaustive approaches are infeasible. 44 44 Winacott and Rudie, 2009 For hybrid systems, such as a switching circuit, Dupuis and Fan compared an LLP supervisor's performance with that of an evolved finite state controller. They concluded that the LLP supervisor was better adapted to systems with slow dynamics and a vector field that flows towards the target, although their study only considered a 1-step lookahead policy for the LLP supervisor.…”
Section: Different Underlying Plantsmentioning
confidence: 99%
“…Limited lookahead control [20], [66] offers a novel solution to the problem of an unmanageable state space. Rather than calculate a complete supervisor offline, which may not be feasible, an N -step "lookahead" tree of possible system behaviour is analyzed to determine control policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A compartmental model undergoes simulation in [11] to compare the cost of approaches to reduce mortality (e.g., universal vaccination and emergency surveillance and response). Pandemic influenza is also a concern; spreadsheet-based software known as FluSurge has been used in [20], [66] Parameterized DES --Mitigates state-space explosion from a supervisory perspective [10] Timed DES Assigns timing intervals to events -No approach to probability; subject to state-space explosion [13], [33] Probabilistic / Stochastic DES -…”
Section: Modelling Health-care Response To a Disastermentioning
confidence: 99%
See 1 more Smart Citation